Roadmap for investment in the seed potato value chain in Eastern Africa - Thiele, Graham; Labarta, Ricardo Antonio; Schulte-Geldermann, Elmar; Harrison, G. (International Potato Center, 2011)
This roadmap describes the five-year strategy in five african countries (Ethiopia, Kenya, Rwanda, Tanzania and Uganda) to target business investments in key areas along the seed potato value chain to increase the availability of high-quality seed potatoes and promote improved seed management. The approaches presented in the rRoadmap are consistent with those laid out in USAID’s comprehensive Feed the Future initiative and are supportive of development themes and programs of other multilateral donors.